Evolution from a first clinical demyelinating event to multiple sclerosis in the REFLEX trial: Regional susceptibility in the conversion to multiple sclerosis at disease onset and its amenability to subcutaneous interferon beta‐1a. (4th April 2022) - Battaglini, Marco; Vrenken, Hugo; Tappa Brocci, Riccardo; Gentile, Giordano; Luchetti, Ludovico; Versteeg, Adriaan; Freedman, Mark S.; Uitdehaag, Bernard M. J.; Kappos, Ludwig; Comi, Giancarlo; Seitzinger, Andrea; Jack, Dominic; et al.
Abstract: Background and purpose: In the REFLEX trial (ClinicalTrials.gov identifier: NCT00404352), patients with a first clinical demyelinating event (FCDE) displayed significantly delayed onset of multiple sclerosis (MS; McDonald criteria) when treated with subcutaneous interferon beta‐1a (sc IFN β‐1a) versus placebo. This post hoc analysis evaluated the effect of sc IFN β‐1a on spatio‐temporal evolution of disease activity, assessed by changes in T2 lesion distribution, in specific brain regions of such patients and its relationship with conversion to MS. Methods: Post hoc analysis of baseline and 24‐month magnetic resonance imaging data from FCDE patients who received sc IFN β‐1a 44 μg once or three times weekly, or placebo in the REFLEX trial. Patients were grouped according to McDonald MS status (converter/non‐converter) or treatment (sc IFN β‐1a/placebo). For each patient group, a baseline lesion probability map (LPM) and longitudinal new/enlarging and shrinking/disappearing LPMs were created. Lesion location/frequency of lesion occurrence were assessed in the white matter. Results: At Month 24, lesion frequency was significantly higher in the anterior thalamic radiation (ATR) and corticospinal tract (CST) of converters versus non‐converters ( p  < 0.05). Additionally, the overall distribution of new/enlarging lesions across the brain at Month 24 was similar in placebo‐ and sc IFN β‐1a‐treated patients (ratio: 0.95). Patients treated with sc IFN β‐1a versus placebo showed significantly lower new lesion frequency in specific brain regions (cluster corrected): ATR ( p  = 0.025), superior longitudinal fasciculus ( p  = 0.042), CST ( p  = 0.048), and inferior longitudinal fasciculus ( p  = 0.048). Conclusions: T2 lesion distribution in specific brain locations predict conversion to McDonald MS and show significantly reduced new lesion occurrence after treatment with sc IFN β‐1a in an FCDE population. Abstract : This post hoc analysis evaluated the effect of subcutaneous interferon beta‐1a (sc IFN β‐1a) on spatio‐temporal evolution of disease activity, assessed by changes in T2 lesion distribution, in specific brain regions of patients with a first clinical demyelinating event (FCDE) and its relationship with conversion to multiple sclerosis (MS; per McDonald criteria). Results showed that T2 lesion distribution in specific brain locations predict conversion to McDonald MS, with significantly reduced new lesion occurrence after treatment with sc IFN β‐1a in an FCDE population